2020
DOI: 10.14198/jhse.2021.161.02
|View full text |Cite
|
Sign up to set email alerts
|

Applying Stage-Based Theory to engage female students in university sport

Abstract: Purpose: University sport is recognized by many as a key area of university strategy and one of increasing importance, as seen by universities prioritizing sport within their university strategic plans as well as national funding bodies investing in university sport. Whilst sport is rising on the agenda, engaging all students in sport is a key challenge for universities. This paper examines the factors that enable and inhibit female students' participation in university sport and active recreation using an int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The meetings lasted a maximum of 45 minutes, each with between 6-9 sport leaders in size that fits with the ideal group size of 6-10 recommended for running a focus group (Morgan, 1997). A post-it note exercise was employed following previous successful practice as illustrated by Brunton and St Quinton (2020). Particularly, students were shown the 15 competencies and asked to write three competencies they felt they were strongest at and three competencies that they feel they needed to improve the most.…”
Section: Methodsmentioning
confidence: 99%
“…The meetings lasted a maximum of 45 minutes, each with between 6-9 sport leaders in size that fits with the ideal group size of 6-10 recommended for running a focus group (Morgan, 1997). A post-it note exercise was employed following previous successful practice as illustrated by Brunton and St Quinton (2020). Particularly, students were shown the 15 competencies and asked to write three competencies they felt they were strongest at and three competencies that they feel they needed to improve the most.…”
Section: Methodsmentioning
confidence: 99%
“…For example, many studies focused on participation constraints such as time and energy, school (e.g., Barney et al, 2019;Diehl et al, 2018;Guo & Ross, 2014;Lerner et al, 2011), required commitment (e.g., St Quinton & Brunton, 2018), skill, competition (e.g., Brunton & St Quinton, 2021;Rundio & Bunning, 2021;Selvaratnam et al, 2021;Shaikh et al, 2018), the equipment, built environment (e.g., Henchy, 2011;Martin & Griffiths, 2016;Spivey & Hritz, 2013) and activity alternatives (e.g., Stankowski et al, 2017). To combat constraints, studies identified participation enablers such as peers (e.g., Webb & Forrester, 2016), the breadth and access to opportunities (e.g., Brunton & St Quinton, 2021;Lower et al, 2015;Snyder et al, 2017;Zuest et al, 2021), financial resources (e.g., Fricke et al, 2018;Wood & Danylchuk, 2015), self efficacy (e.g., Lower-Hoppe et al, 2021) and previous experience (Lyons et al, 2018. Studies also explored the motivational factors of participation such as socialization/peer support, competency/mastery (e.g., Beggs et al, 2014;Carter-Francique, 2011;Deng et al, 2021;Ramos et al, 2018), appearance (e.g., Cooper et al, 2012;Diehl et al, 2018), goal achievement (e.g., Lower-Hoppe et al, 2021;Snyder et al, 2017), entertainment/stimulation (e.g., Munusturalar et al, 2015;Shapiro et al, 2020). A few studies also investigated communication and marketing practices like information dissemination (e.g., Lee et al, 2020), the use of social media (e.g., ...…”
Section: Themesmentioning
confidence: 99%